Relationship of factors professionals, academics and teaching skills of the teacher of the catholic University of Trujillo - Rosas Prado, Carmen Elvira (2015)
The present investigation had as intention determine the level of relation of the professional, academic factors and the pedagogic competitions of the teacher of the Catholic University of Trujillo; bearing in mind that the professional factors, they correspond to the professional experience to educational level and his pedagogic formation, the academic factors correspond to the academic level reached by the teachers (professional title, the second professionalization, degree of teacher and of doctor) and that the pedagogic competitions correspond to three dimensions cognitive competitions, procedural competitions and competitions actitudinales, there was verified that significant relation exists between variable professional, academic factors and pedagogic competitions, the above mentioned result It was established by means of the utilization of the coefficient of Pearson’s correlation.